Automated green sample preparation for quantitative extraction of lipids in different sample matrices - Pia Wittenhofer; Lidia Montero; Oliver J. Schmitz; Sven W. Meckelmann (Green Analytical Chemistry, 2024)
An essential step in all analytical workflows is the quantitative and robust extraction of the molecules of interest. While typical lipid extractions use hazardous solvents from non-renewable sources, in this work, an extraction protocol utilizing green solvents such as ethanol and ethyl acetate is presented. The workflow was also automated to reduce variability and increase robustness as well as sample throughput. Moreover, this minimizes the contamination risks and lowers the operator's exposure to organic solvents. The developed workflow was critically evaluated by the recovery of various lipid standards from different matrices (human plasma, human serum, HepG2 cells) yielding quantitative values around 80–90 % for most lipid classes. The investigation into concentration dependency reveals the robustness of the method, demonstrating consistent recoveries across various lipid concentrations and matrix contents. In non-targeted lipidomics analyses, the green solvents proved to be comparable to established protocols that use conventional solvents such as methyl‑tert-butylether (MTBE) for lipid extraction.